De Cuauhtemotzín a las cervecerías. El control oficial del homoerotismo masculino y la construcción estratégica de la geografía disidente, ciudad de México, 1930-1951 - Rodríguez Sánchez, Nathaly (El Colegio de México, A.C., 2018)
Through a critical dialogue with the historical approaches to sexual heterodoxy based around the hypothesis of strict social control, which implies a state of inaction among those who have such desires, this article explores the forms of official control over homoerotic practices that were effectively implemented in Mexico City during the postrevolutionary period, reconstructing the spaces and strategies that provided a space for dissidence. By examining the mark left by these social control measures on the El Carmen Prison, which has been little studied until now, it can be seen that official persecution was limited - in comparison with other contexts and periods, as there was no penal classification of these practices in Mexico-inconstant– as it was a response to certain periods of “moral panic” in which social prejudices were exacerbated –and porous– as class position was a determining factor in its application. This context was strategically read by men with a homoerotic orientation. Instead of silent, passive objects of censure, this article reveals that individuals interacted with these conditions to construct a dissident geography.